Tailoring the electronic structure and magnetic properties of pyrochlore Co2Ti1−xGexO4: a GGA + Uab initio study. (16th February 2021) - Ghosh, Sayandeep; Singh, Sobhit; Das, Debashish; Ghosh, Subhradip; Mishra, Pankaj Kumar; Thota, Subhash
Abstract: We report the electronic structure and magnetic properties of Co2 Ti1− x Ge x O4 (0 ⩽ x ⩽ 1) spinel by means of the first-principle methods of density functional theory involving generalized gradient approximation along with the on-site Coulomb interaction ( U eff ) in the exchange-correlation energy functional. Special emphasis has been given to explore the site occupancy of Ge atoms in the spinel lattice by introducing the cationic disorder parameter ( y ) which is done in such a way that one can tailor the pyrochlore geometry and determine the electronic/magnetic structure quantitatively. For all the compositions ( x ), the system exhibits weak tetragonal distortion ( c / a ≠ 1) due to the non-degenerate d z 2 and d x 2 − y 2 states ( e g orbitals) of the B-site Co. We observe large exchange splitting (ΔEX ∼ 9 eV) between the up and down spin bands of t 2 g and e g states, respectively, of tetrahedral and octahedral Co 2+ ( 4 A2( g ) (F)) and moderate crystal-field splitting (ΔCF ∼ 4 eV) and the Jahn–Teller distortion (ΔJT ∼ 0.9 eV). These features indicate the strong intra-atomic interaction which is also responsible for the alteration of energy band-gap (1.7 eV ⩽ E g ⩽ 3.3 eV). The exchange interaction ( J BB ∼ −4.8 meV, for ( x, y ) = (0.25, 0)) between the Co 2+ dominates the overall antiferromagnetic behaviour of the system for all ' x ' as compared to J AA (∼−2.2 meV, for ( x, y ) = (0.25, 0)) and J AB (∼−1.8 meV, for ( x, y ) = (0.25, 0)). For all the compositions without any disorderness in the system, the net ferrimagnetic moment (Δ μ ) remains constant, however, increases progressively with increasing x due to the imbalance of Co spins between the A- and B-sites.